Institutional Intervention and the Feminization of Farm Sector: Lessons of Experiments with KDMS and MKSP in Kerala - B.Pradeep Kumar
Two transitions-the migration of male workers to urban areas in pursuit of remunerative jobs and the growing discontentment among the farmers with regard to the expectation of farm profits-that the farm sector has seen recently are said to be contributing to the evolution of a kind of transformation in Indian farm sector which is nothing but an emerging phenomenon of feminization of farm activities. But the grey side of this seemingly inevitable transformation lies in the distribution of land holdings, a kind of gender disparity in the distribution of operational holdings, which, given institutional interventions like the KDMS, can be solved in future. The advent of MKSP has given fillip to the process of farm feminization in Kerala. These bright aspects notwithstanding, certain systemic lacuna have been found in the functioning of MKSP under the KDMS model. The field study unequivocally raises certain apprehensions as to the excessive political interference camouflaged in the functioning of the programme. The study also calls for the effective institutional interventions in enhancing the effectiveness of MKSP in accelerating the pace of feminization of farm sector.